(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The application of new discoveries and innovative technologies in the field of education helps to improve the quality of education. Educational Technology mainly comprises of hardware, software and instructional design. It can be said, undoubtedly, that educational technology is a technology through which we can make educational process more easy and effective. When the communication technology is integrated with Information Technology, the Information and Communication Technology is formed. The use of ICT in education has a huge potential for the enrichment in formal education system. ICT can be utilized as an informative, constructive and communicative tool. Thus, ICT has the potential to utilize in almost all the processes of education like teaching learning process, administration of the institution, managerial, clerical, laboratory, library etc. For evaluation purpose, computer software is used to evaluate the students learning. It is easier for teachers to evaluate answer sheets of students with its help. It also helps in conducting various exams viz. admission tests, monthly tests, yearly tests, and keeping and maintaining the records. One such important use of software in education is management. Managing activities is the newer application of computer software. The software aspect of Information Technology mainly comprises of management information system and decision support system. In this article we will study about the result of implementing the student information management techniques in the Secondary schools of Jaipur city, Rajasthan.